Pengaruh Trust Dan Commitment Terhadap Relationship Quality Studi pada Perusahaan Pasangan Usaha PT. XYZ (Sebuah Lembaga Keuangan Non Bank) - Reza Rahardian (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2011)
This study aims to describe the business partner companies perceived of trust, commitment and relationship quality at PT. XYZ (a non bank financial institution). Theoritically, this research aims to provide empirical evidence of the influence of trust and commitment on relationship quality, and the mediation effect of commitment to the influence of trust towars the relationship quality. Data were gathered from 31 business partner companies of PT. XYZ. Multiple Regression/Path Analysis was used to test the hypotheses. Descriptive analysis shows that there is a high trust and commitment in business partner companies of PT. XYZ. They also give a high respons to the relationship quality. Regression analysis shows that trust and commitment influence the relationship quality. It also revealed that there isi mediation effect of commitment to the influence of trust towards relationship quality. This study has limitation by using respondent perceived only. This can be overcome by conducting comparative analysis using actual performance indicator evaluated by PT. XYZ.